2009
DOI: 10.1249/mss.0b013e3181951314
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Fitness of the Caregiver of Patient with Dementia

Abstract: : Relative to the standard exercise programs of the general population, exercise programs for female caregivers should be more focused on preventing back pain by developing the endurance strength of the trunk extensors. A supervised exercise program including the interaction between caregiver and health professional could also help to minimize the psychosocial components that affect the health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 23 publications
6
50
1
5
Order By: Relevance
“…Yet, their HRQoL, in terms of mental health, was significantly poorer than that of their peers in the same age or gender groups. These results are supported by findings from previous studies, conducted in other countries [7,10]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Yet, their HRQoL, in terms of mental health, was significantly poorer than that of their peers in the same age or gender groups. These results are supported by findings from previous studies, conducted in other countries [7,10]. …”
Section: Discussionsupporting
confidence: 92%
“…Research has also shown that caring for relatives with dementia is a long-term and stressful experience and can impair the HRQoL of family caregivers [6,7,8,9,10]. For service providers, improving HRQoL is an indispensable part of determining effective interventions for the vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted health promotion may benefit female caregivers, who take part in fewer health promoting activities than men (Gibbons et al, 2014). For instance, one Spanish study showed that, although overall physical health of female caregivers caring for a person with dementia was similar to non-caregivers, the caregiver group smoked more and were more likely to classify themselves as being physically inactive (Gusi et al, 2009). There are differences between kinship groups; daughter caregivers were more likely to have experienced recent weight gain, and develop high blood pressure than spousal caregivers (Rabinowitz & Gallagher-Thompson, 2007).…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Targeting specific interventions designed for particular kinship or ethnic groups, may help address specific patterns of health behaviours and conditions needed to improve health outcomes, and maintain caregiver health in order to provide adequate care (Gusi et al, 2009;Rabinowitz & Gallagher-Thompson, 2007, Godfrey & El-Badri, 2009Godfrey & Warshaw, 2009).…”
Section: Coping Strategiesmentioning
confidence: 99%